Muslims’ Responses towards Orientalists’ ‎views on Hadis as the Second Source of Law in ‎Islam with special Reference to Mustafa al-‎Siba’i’s Criticism Toward Ignaz Goldziher’s ‎Viewpoints - sanuri sanuri (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2009)
One of the orientalists’ objects in learning Islam is hadis as the second source of law in Islam. Ignaz Goldziher is the most representative and notable orientalist to talk and criticize hadis as rather scientific research of the second and third century of Hijriyah than originally steamed from the original source, he is prophet Muhammad. On the other hands, most of Muslim scholars strongly objected to such viewpoint. One of those who disagreed to the accusation is Mustafa al-Siba’iy. He proved the authenticity of hadis by conveying the historical approach argumentations. He had a conclusion that historically, hadis transmission had been started since the prophet Muhammad’s period though he never officially assigned to his companions but they intensively wrote hadis as a self-documentation. To strengthen his theory, he offered some rational argumentations; (1) traveling (rihlah) tradition (2) tracing isnad (link) of hadis (3) authenticity of hadis (tauthiq al-hadith) (4) narrator criticism methodology.